Conhecimento e atividades de autocuidado dos portadores de Diabetes Mellitus tipo 2: fatores associados - Silva, Clarissa Galvão da (2016)
The Diabetes mellitus (DM) is a heterogeneous group of metabolic disorders has in common hyperglycemia, result from defects in insulin action or insulin secretion or both. This is one of the health problems of greater magnitude in Brazil. So the selfcare activities are essential in carriers of diabetes mellitus type two to maintain and improve their health. However represent challenge for carries and health professionals. The research aimed to analyze the factors associated to knowledge about diabetes and to self-care activities of carries of Diabetes mellitus type two. For that was conducted a cross-sectional analytical study with a quantitative approach with 360 carries of diabetes mellitus type two attended at Ambulatory Endocrinology of Federal University of Maranhão. The data collect was conducted in the period from february to july 2015. For data collection was used three instruments, one containing identification data with open and closed questions concerning sociodemographic and clinical variables, self-care activities questionnaire with Diabetes (QAD) and questionnaire of scale knowledge of Diabetes (DKN). We used Spearman coefficient in the correlation between self-care activities with age and time of disease, the MannWhitney test for association of self-care of scores with the sociodemographic and clinical variables and the Chi Square test to association between knowledge and sociodemographic and clinical variables. For interpretation of statistic has adapted results the significance level of 5% (p < 0.05). The research has shown that carries of diabetes mellitus type 2 have generally low self-care for items general food, physical activity and monitory glycemia and the best self-care activities are related the specific food, medication and care of the feet. Observed that most participants had higher scores to 8, indicates a high degree of knowledge about disease. If found associations between the scores of knowledge and self-care activities with the socioeconomic and clinical variables. It was concluded that there are factors related to socioeconomic and clinical features that interfere with the self-care activities and the knowledge of carries with diabetes mellitus type 2 against disease.